2013
DOI: 10.1007/s00167-013-2402-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of WOMAC and KOOS scores to tibiofemoral cartilage loss on plain radiography and 3 Tesla MRI: data from the osteoarthritis initiative

Abstract: The WOMAC and KOOS scores are poor indicators of tibiofemoral cartilage loss, with only the KOOS symptom and knee pain score being weakly correlated. Osteoarthritis is a multifactorial process and the need to treat patients based off their symptoms and rely on radiographs as confirmatory modalities, and not diagnostic modalities, when talking about OA and medical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Medial and lateral JSN were both strong predictors of cartilage loss in the narrowed, but not in the non-narrowed joint compartment 69. Further, frequently painful knees displayed greater cartilage loss than those without pain, also after adjusting for radiographic stage,68 70 but no correlation was detected for other pain scores 37. Comparing cartilage change over 1–4-year periods,71 72 the mean loss (but not the SRM) scaled linearly with observation length and was constant throughout the study, but only weak to moderate agreement was observed between individual short-term versus long-term change 72.…”
Section: Imaging Publications From Full Cohort Releasesmentioning
confidence: 89%
See 3 more Smart Citations
“…Medial and lateral JSN were both strong predictors of cartilage loss in the narrowed, but not in the non-narrowed joint compartment 69. Further, frequently painful knees displayed greater cartilage loss than those without pain, also after adjusting for radiographic stage,68 70 but no correlation was detected for other pain scores 37. Comparing cartilage change over 1–4-year periods,71 72 the mean loss (but not the SRM) scaled linearly with observation length and was constant throughout the study, but only weak to moderate agreement was observed between individual short-term versus long-term change 72.…”
Section: Imaging Publications From Full Cohort Releasesmentioning
confidence: 89%
“…Cross-sectionally, JSN and KOOS symptom scores were weakly correlated 37. Longitudinally, radiographic change was significantly correlated with worsening pain and function scores 40.…”
Section: Imaging Publications From Full Cohort Releasesmentioning
confidence: 94%
See 2 more Smart Citations
“…Illingworth et al (18) found the Womac and Knee Injury Osteoarthritis Outcomes scores as poor indicators for cartilage loss. However, Torres et al (19) found the severity of knee pain associated with meniscal tears additionally to subarticular bone attrition, bone marrow lesions and synovitis.…”
Section: Discussionmentioning
confidence: 99%